Mitoregulin, a tiny protein at the crossroads of mitochondrial functioning, stress, and disease - Sergiev, Petr; Averina, Olga; Golubeva, Julia; Vyssokikh, Mikhail; Dontsova, Olga (Frontiers in Cell and Developmental Biology, 2025)
Mitoregulin (Mtln) is a small mitochondrial protein that was only recently identified. Despite this, a substantial number of studies on its function have already been published. Although sometimes contradictory, these studies have revealed the localization of Mtln, its protein and lipid partners, and its role in lipid homeostasis, energy metabolism, oxidative stress, and other aspects of mitochondrial functioning. Moreover, research using knockout and transgenic mouse models has revealed the important role of Mtln in mammalian physiology. Metabolic changes, along with muscle, kidney, and fat-related phenotypes, have been linked to Mtln dysfunction. In this review, we summarize a comprehensive set of published data on Mtln. While controversies remain, we seek to offer a unified view of its functions, spanning molecular mechanisms to organism-level effects.